Minimally invasive and remote‐access thyroid surgery in the era of the 2015 American Thyroid Association guidelines. Issue 6 (14th November 2016) - Russell, Jonathon O.; Noureldine, Salem I.; Al Khadem, Mai G.; Tufano, Ralph P.
Abstract : Thyroid surgery has evolved throughout the years from being one of the most dangerous surgeries to becoming one of the safest surgical procedures performed today. Recent technologic innovations have allowed surgeons to remove the thyroid gland from a remote site while avoiding visible neck scars. There are many endoscopic approaches for thyroidectomy. The most common cervical approach is the minimally invasive video‐assisted technique developed by Miccoli et al. The robotic transaxillary and axillary breast approaches avoid a neck scar and have been demonstrated to be safe and effective in international populations. Novel approaches under investigation include face‐lift robotic thyroidectomy and the transoral approach. This article aims to provide the reader with an overview of the current minimally invasive and alternate‐site approaches used and their capability to assist the surgeons in accomplishing remote‐access thyroid surgery under the scope of the 2015 American Thyroid Association Guidelines.